Redefining the History and Historiography on American Evangelicalism in the Era of the Religious Right - Sutton, Matthew Avery (Journal of the American Academy of Religion, 2024)
Writing in the shadow of the religious right, a group of historians beginning in the 1980s crafted a new history of American evangelicalism to counter the politicized, right-wing faith of their era. Rather than focus on the movement as a product of specific historical, cultural, and political contexts, they defined it by a set of abstract theological principles. Then they identified those people from the colonial period to the present who fit their definition and who made positive contributions to North American history. The result was a new, singular, multi-century, "evangelical consensus" in the literature that decoupled the movement from politics, race, class, gender, and sexuality. I assess the historiography they created and then argue that we should drop the use of the term evangelical from our eighteenth- and nineteenth-century histories, and I offer a new definition of postwar evangelicalism that embeds it in its cultural context.